Laser hemorrhoidoplasty versus Milligan-Morgan hemorrhoidectomy – short-term outcome - Maloku, Halit; Lazović, Ranko; Terziqi, Hasime (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. According to the “vascular” theory, arterial inflow into the upper hemorrhoidal artery leads to venous dilatation of the hemorrhoidal plexus. Laser hemorrhoidoplasty (LHP) is a new treatment applied to outpatients in whom the hemorrhoid arterial blood flow is coagulated (nourishes by hemorrhoidal plexus) by laser. The aim of this study was to compare two groups of patients treated by two different methods: by laser (LHP) and with open surgical procedure – the Milligan Morgan (MM) method. Methods. This study included 200 patients with grade 3 hemorrhoidal disease older than 18 years, divided into two groups: 100 patients treated with the LHP, while the other 100 patients with the MM hemorrhoidectomy. Parameters used to compare two applied surgical methods were: duration of hospitalization, postoperative pain, the presence of bleeding and time needed to return to normal life. Results. The results reveal a statistically significant difference between these two methods. The level of postoperative pain was lower in the group of patients treated with the LHP compared to the group of patients treated with the MM method (p
Keywords: hemorrhoids; laser therapy; surgical procedures, operative; postoperative period; postoperative complications.